The Teachers Union-Charter Impasse: Moving Forward from the New York Caps Fight - Stulberg, Lisa Michele (Education Policy Analysis Archives, 2010)
The public narrative generally frames teachers unions and the charter movement as mistrustful opponents locked in an unresolved impasse. There is little scholarly literature to correct this simplistic narrative of the relationship between charters and unions. This article examines the teachers union- charter relationship through a recent case of active and sometimes bitter charter politics: the fight to lift the charter cap in New York state in 2006 and 2007. This study examines the dynamics of the relationship through an analysis of media coverage of the New York caps fight and interviews with nearly 30 experts with varied views on charter schooling and from a wide range of professional backgrounds. The New York case suggests that ultimately, creating strong unions and effective charter schooling depends on these two sides finding common ground.